G362(P) Recommendations from the revision of the RCPCH pathways to diagnosis: The diagnosis of brain tumours guideline. (27th April 2016) - Shanmugavadivel, D; Wilne, S; Liu, JF; Walker, DA
Abstract : Aims: The RCPCH guideline entitled Pathways to Diagnosis: The Diagnosis of Brain Tumours was published in 2008 and later accredited by NHS (NICE) Evidence. The HeadSmart: Be Brain tumour aware campaign was launched in 2011 to amplify the guidance and has successfully halved the total diagnostic interval in the UK. We are conducting a systematic review and meta-analysis in order to update the guideline using current published evidence. Methods: Medline, Pubmed and Embase databases were searched without language restriction from January 2005–August 2015. Key words were "brain tumour (s)", "brain tumour (s)", "brain neoplasm (s)", "diagnosis", "signs (s)", "symptom (s)", "presentation (s)". All references were restricted to "all child". All papers containing data of brain tumour presentation, diagnosis or presenting signs and symptoms were included. A standard data extraction form was used to record the numbers of children with each symptom/sign. Some studies were detailed on individual symptoms (headache, vomiting, papilloedema) whilst others recorded complexes (eg intracranial pressure). If a symptom/sign was not recorded, it was assumed not to have occurred in that population. Results: 20, 068 papers were identified by the search terms. We reviewed 664 papers in full of which 71 met the inclusion criteria describing the signs and symptoms in 3818 children. A total of 152 symptoms were identified of which 80% presented with signs and symptoms of raised intracranial pressure (including headache and vomiting). Visual symptoms (16%), ataxia (11%), CN palsies (10%) and seizures (9%) together with raised ICP made up the top 5 presenting signs/symptoms. HeadSmart data shows that children with midline supratentorial tumours and adolescents have the longest total diagnostic intervals. Subgroup analyses of tumour location, children under the age of 2, and young people is ongoing. Where no substantial clinical research evidence is identified, a formal consensus method will be used to formulate recommendations. Conclusions: Our HeadSmart data has given us valuable guidance as to which subgroups to focus this analysis on. The presentation will summarise the new recommendations which will help us meet the government target of all cancer diagnoses within 4 weeks. The revised draft guideline will be discussed at the conference.